Persuasive Communication in Indonesian Digital Tourism Promotion: Destination Branding, Local Identity, and Tourist Engagement - Suhartina Suhartina; Andi Nurindahsari (CV. Austronesia Akademika, 2026)
Digital tourism promotion has transformed the way destinations are communicated, imagined, and selected by potential tourists. In Indonesia, tourism advertisements found through Google search results and Google Images widely use persuasive language and visual design to attract audiences, promote travel packages, and construct destination images. This study aims to examine how persuasive communication is used in Indonesian digital tourism advertisements, how verbal and visual elements construct destination branding, and how these advertisements represent local identity, tourist segmentation, and multimodal tourism promotion. This research employed a qualitative design with descriptive digital content analysis. The data consisted of 30 digital tourism advertisements in the form of posters, flyers, and online tourism brochures promoting Indonesian destinations. The data were selected through purposive sampling based on destination relevance, persuasive text, visual clarity, promotional content, and public accessibility through Google search results. The findings show that persuasive language is constructed through direct invitations, price emphasis, promotional claims, service assurance, and experiential expressions such as “Book Now,” “Promo,” “Start From,” “Paket Murah,” and “Liburan Yuk.” Visual elements such as beaches, mountains, temples, lakes, islands, cultural icons, and tourism activities strengthen destination branding and shape tourist imagination. The findings also reveal that local identity and tourist segmentation are represented through halal trip, honeymoon, study tour, open trip, private tour, family trip, and budget tourism packages. This study concludes that Indonesian digital tourism advertisements function as multimodal promotional texts that integrate language, image, price, facilities, itinerary, and booking information to strengthen destination branding.